Assessment of water quality of streams in northeast Turkey by water quality index and multiple statistical methods. Issue 1 (3rd April 2021) - Aydin, Handan; Ustaoğlu, Fikret; Tepe, Yalçın; Soylu, Elif Neyran
Abstract: A year-long study from May 2018 to April 2019 investigated the spatio-temporal changes in water quality of seven major rivers in the Giresun Province in northeastern Turkey. The results of the analysis were classified according to WHO limit values for drinking water and water quality classes were determined with respect to the Turkish Surface Water Quality Regulation (TSWQR). In addition, sodium percentage (% Na), sodium absorption ratio (SAR), magnesium hazard (MH), and residual sodium carbonate (RSC) values were calculated to evaluate the eligibility of the streams for irrigation purposes. Multivariate statistical analysis methods such as one-way ANOVA, Pearson correlation index (PCI), cluster analysis (CA), principal components analysis/factor analysis (PCA/FA) were used to determine the differences and similarities of streams, pollution sources and relations between parameters. As a result of the PCA, four factors accounted for 71.52% of all factors. These factors show that the major changes in water quality parameters were associated with point-based pollution such as wastewater from household and industrial resources, non-point sources such as agricultural activities and natural phenomena such as flooding, rock and soil erosion. The pH values in the range of 7.77 to 9.8 were slightly alkaline compared to the TSWQR range of pH 6–9. In certain months, the average NO2 -N values (> 0.06 mg/L) in Batlama Stream, Aksu Stream, Yağlıdere Stream and Gelevera Stream was class III (medium) water quality and mean fluoride values in streams (1 and 1.19 mg/L) were class II water quality according to TSWQR. The levels of anionic surfactants in all streams were class III (polluted) water quality, except for Pazarsuyu Stream with class II (less polluted) water quality. The annual mean water quality index (WQI) values of the streams ranged from 25.69 (excellent) to 32.39 (good). When the water quality was evaluated for irrigation, the SAR, Na%, RSC and MH did not exceed the limit values. Based on these indices it was assessed that settlements and related anthropogenic activities along the riverbanks did not affect the water quality currently. This does not mean that it may not have an effect in the near future.